Coordination polymers of Fe(III) and Al(III) ions with TCA ligand: distinctive fluorescence, CO2 uptake, redox-activity and oxygen evolution reaction - Dhara, Barun; Sappati, Subrahmanyam; Singh, Santosh K.; Kurungot, Sreekumar; Ghosh, Prasenjit; Ballav, Nirmalya (Dalton Transactions, 2016)
Fe and Al belong to different groups in the periodic table, one from the p-block and the other from the d-block. In spite of their different groups, they have the similarity of exhibiting a stable 3+ oxidation state. Here we have prepared Fe(III) and Al(III) based coordination polymers in the form of metal-organic gels with the 4,4', 4 `'-tricarboxyltriphenylamine (TCA) ligand, namely Fe-TCA and Al-TCA, and evaluated some important physicochemical properties. Specifically, the electrical conductivity, redox-activity, porosity, and electrocatalytic activity (oxygen evolution reaction) of the Fe-TCA system were noted to be remarkably higher than those of the Al-TCA system. As for the photophysical properties, almost complete quenching of the fluorescence originating from TCA was observed in case of the Fe-TCA system, whereas for the Al-TCA system a significant retention of fluorescence with red-shifted emission was observed. Quantum mechanical calculations based on density functional theory (DFT) were performed to unravel the origin of such discriminative behaviour of these coordination polymer systems.

High-index faceted Au nanocrystals with highly controllable optical properties and electro-catalytic activity - Rajendra, Ranguwar; Gangadharan, Pranav K.; Tripathi, Shalini; Kurungot, Sreekumar; Ballav, Nirmalya (Nanoscale, 2016)
We introduce a new and naturally abundant mild reducing agent, tannic acid, to improve the seed-mediated growth method for the synthesis of elongated tetrahexahedral Au nanocrystals enclosed with high-index (730) planes, at room-temperature. The control of the dimensions, plasmonics and electro-catalysis of such high-index faceted nanocrystals is remarkable.

Pb2+-N bonding chemistry: recycling of polyaniline-pb nanocrystals waste for generating high-performance supercapacitor electrodes - Jha, Plawan Kumar; Singh, Santosh K.; Gatla, Suresh; Mathon, Olivier; Kurungot, Sreekumar; Ballav, Nirmalya (Journal of Physical Chemistry C, 2016)
Understanding of Pb-N bonding chemistry is not only fundamentally important in the view of relativistic inert-pair effect but also is important for therapeutic as well as environmental applications. In the present study, an unusual reactivity of N-containing pi-conjugated polyaniline emeraldine base (EB) toward aqueous Pb2+ ions has been identified. In the course of sequestering Pb2+ ions by EB, cuboid-shaped nanocrystals were isolated. Synchrotron-based X-ray absorption near-edge structure and extended X-ray absorption fine structure techniques were employed to understand Pb-N bonding chemistry in EB-Pb nanocrystals. The adopted methodology of slow exposure of HCl vapor to EB-Pb nanomaterial facilitated the isolation of polyaniline emeraldine-salt (ES) with unique morphological patterns, porosity and electrical conductivity. The electrochemical device based on recycled ES showed high-capacitance value (similar to 606 F/g @1 A/g and similar to 663 F/g @10 mV/s), high-energy density (similar to 14.8 Wh/kg at power density of similar to 663 W/kg) and excellent-cycling stability (only similar to 15% degradation after 1100 continued cycles at current density of 5 A/g). Notably, ES materials prepared directly from EB and upon exposing HNO3 vapor exhibited greatly inferior device performance.

Cisplatin-induced self-assembly of graphene oxide sheets into spherical nanoparticles for damaging sub-cellular DNA - Nandi, Aditi; Mallick, Abhik; More, Piyush; Sengupta, Poulomi; Ballav, Nirmalya; Basu, Sudipta (Chemical Communications, 2017)
This report describes the hitherto unobserved cisplatin induced self-assembly of 2D-graphene oxide sheets into 3D-spherical nano-scale particles. These nanoparticles can encompass dual DNA damaging drugs simultaneously. A combination of confocal microscopy, gel electrophoresis and flow cytometry studies clearly demonstrated that these novel nanoparticles can internalize into cancer cells by endocytosis, localize into lysosomes, and damage DNA, leading to apoptosis. Cell viability assays indicated that these nanoparticles were more cytotoxic towards cancer cells compared to healthy cells.

High-level supercapacitive performance of chemically reduced graphene oxide - Jha, Plawan Kumar; Singh, Santosh Kumar; Kumar, Vikash; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Chem, 2017)
Reduction of graphene oxide (GO) is an important process because it holds promise for the production of reduced graphene oxide (rGO) with physicochemical properties similar to those of pristine graphene. In conventional chemical reduction, strong reducing agents, such as sodium borohydride and hydrazine, cannot be recycled. Also, fast reaction kinetics bring an imbalance in the desirable properties of rGO. Here, we present one-pot chemical reduction of GO in aqueous medium by an unconventional mild reducing agent (FeCl2/HCl) where rGOis isolated as the precipitate and the reducing agent is recycled upon simple treatment of the filtrate with HCl. The fabricated all-solid-state supercapacitors of as-synthesized rGO exhibited significantly higher specific capacitance than those obtained with rGO derived from conventional reducing agents. The cycling stability of the all-solid-state supercapacitor (> 80% retention of capacitance beyond 100,000 continued cycles) and its flexibility (> 500 bending cycles) were remarkable. Use of commercially available organic electrolyte further boosted the supercapacitor performance.

Metamagnetism in nanosheets of Co-II-MOF with T-N at 26 K and a giant hysteretic effect at 5 K - Gupta, Kriti; Dadwal, Arun; Rana, Shammi; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2018)
Herein, we have synthesized at room-temperature two-dimensional nanosheets of a MOF comprised of cobalt(II) ion with benzenedicarboxylic acid ligand, which exhibited unusual magnetic properties. Direct-current magnetic susceptibility revealed an anti-ferromagnetic (AFM) transition at 26 K (Neel temperature, T-N) followed by a canting of the spin moments along with the concomitant appearance of a sigmoidal-shaped magnetization versus field (M-H) curve at 15 K. Such a canted AFM ordering led to nonzero remnant magnetization with a remarkably high coercive field of similar to 10 kOe at 5 K. Metamagnetism was further: substantiated by the alternating-current magnetic susceptibility measurements.

Embedding S=1/2 Kagome-like lattice in reduced graphene oxide - Gupta, Kriti; Jha, Plawan Kumar; Dadwal, Arun; Debnath, Anil K.; Jaiswal, Ishan; Rana, Shammi; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry Letters, 2019)
An elegant platform to explore frustrated magnetism is the kagome spin lattice. In this work, clinoatacamite, a naturally occurring S = 1/2 kagome-like antiferromagnetic insulator, is synthesized in water at ambient pressure for the first time from a cuprous chloride (CuCl) precursor whereby Cu(I) was spontaneously oxidized to Cu(II) in the form of clinoatacamite [Cu-2(OH)(3)Cl] with a simultaneous reduction of graphene oxide (GO) to reduced graphene oxide (rGO) in one pot. A stable nanocomposite of phase-pure clinoatacamite nanocrystals embedded in the rGO matrix was isolated. The clinoatacamite-rGO nanocomposite was determined to be magnetically active with a markedly enhanced coercive field of similar to 2500 Oe at S K as well as electronically active with a conductivity value of similar to 200 S.m(-1) at 300 K. Our results illustrate an avenue of combining exotic magnetic and electronic lattices without impeding their individual characteristics and synergistically generating a new class of magnetic semiconductors.

In-situ generated Mn3O4-reduced graphene oxide nanocomposite for oxygen reduction reaction and isolated reduced graphene oxide for supercapacitor applications - Jha, Plawan Kumar; Kashyap, Varchaswal; Gupta, Kriti; Kumar, Vikash; Debnath, Anil Krishna; Roy, Debashree; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Carbon, 2019)
We have generated in situ nanocomposite of Mn3O4 and reduced graphene oxide (rGO) upon employing wet-chemical reduction of graphene oxide (GO) by Mn(II) salt as mild-reducing agent for the first time and examined the oxygen reduction reaction (ORR) activity in 0.1 M KOH electrolyte. The half-wave potential (E-1/2) of the nanocomposite catalyst (20% Mn3O4-rGO/C) was found to be around -0.153 V which is only similar to 87 mV negative from the commercially available catalyst (20% Pt/C). Remarkably, after 5000 linear sweep voltammetry cycles the E-1/2 shifted marginally by 20 mV; and the number of electrons transferred during ORR was estimated to be close to 4. Such an efficient electrocatalytic performance of the nanocomposite was primarily attributed to the synergistic interaction between Mn3O4 and rGO. The fabricated all-solid-state supercapacitor of rGO (extracted from the nanocomposite) in aqueous polyvinyl alcohol-sulfuric acid (PVA-H2SO4) gel polymer electrolyte (GPE) showed C-s value of similar to 310 F/g at a current density of 1 A/g along with long durability (10,000 charge-discharge cycles). All-solid-state flexible rGO supercapacitor exhibited high-flexibility and excellent durability (30,000 cycles with 100% retention of C-s). Our results provide an enormous opportunity in designing transition metal oxides decorated semiconducting reduced graphene oxide nanocomposite platforms for various electrochemical applications. (C) 2019 Elsevier Ltd. All rights reserved.

Exploring magnetic XY behavior in a quasi-2D anisotropic triangular lattice of Cu(II) by functionalized graphene - Gupta, Kriti; Dadwal, Arun; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2020)
Study on magnetism in two-dimensional (2D) spin-lattices is advancing rapidly. In this work, phase-pure botallackite (Bo) (Cu-2(OH)(3)Br), a quasi-2D S = 1/2 anisotropic triangular spin-lattice is stabilized over 2D reduced graphene oxide (rGO) nanosheets via simple oxidation-reduction reaction chemistry. In comparison to polycrystalline Bo, such an anchoring resulted in the oriented growth of Bo crystallites in the Bo-rGO system. The Bo-rGO nanocomposite was found to be magnetically active with a Neel transition at 8.9 K, crossing over to possible XY anisotropy at similar to 5 K-as revealed by complementary dc and ac susceptibility measurements-an unprecedented observation in the field assigned to an interfacial effect. This work demonstrates the potential usage of nonmagnetic 2D functionalized graphene to significantly modulate the magnetic properties of 2D spin-lattices.

Integrating structurally perfect s=1/2 kagome-lattice with reduced graphene oxide - Gupta, Kriti; Dadwal, Arun; Ninawe, Pranay; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry C, 2020)
S = 1/2 kagome-lattice hydroxychlorides are promising candidates for realizing the elusive quantum spin liquid (QSL) state. Herbertsmithite [Cu3Zn(OH)(6)Cl-2], a naturally occurring hydroxychloride mineral from the class of atacamites {[Cu-4-xMx(OH)(6)X-2] where M = Zn, Cu, Co, Ni and X = Cl, Br, I}, is one of the most appealing systems to study the QSL state because of the presence of a structurally perfect S = 1/2 kagome-lattice. It is an electrical insulator. However, realizing phase-pure herbertsmithite without imposing harsh reaction conditions remained synthetically challenging. In this work, for the first time, we have synthesized phase-pure herbertsmithite as well as its structural analogue paratacamite, [ZnxCu4-x(OH)(6)Cl-2; 0.33 = x < 1], at ambient reaction conditions. Furthermore, taking graphene oxide (GO) as an additional precursor in the reaction mixture, we have successfully integrated phase-pure crystallites of herbertsmithite (H) and paratacamite (P) with nanosheets of semiconducting and diamagnetic reduced graphene oxide (rGO) by in situ oxidation-reduction reaction. The isolated H-rGO and P-rGO systems were found to be magnetic semiconductors inheriting strong spin frustration from H and P, and semiconductivity from rGO. The H-rGO system in particular exhibited negative Seebeck coefficient (n-type semiconductor) with a thermoelectric power factor of 0.1 mu W center dot m(-1)center dot K-2 at 400 K. We anticipate the simple chemical principles outlined in this work to be useful for studying a variety of complex QSLs including electron doping. Also, semiconducting and rather unconventional materials of such metal oxochlorides with rGO isolated here need further exploration in view of thermoelectric applications.

Magnetism in bimetallic NiII-CoII coordination polymer - Gupta, Kriti; Dadwal, Arun; Joy, Pattayil; Ballav, Nirmalya (AIP Conference Proceedings, 2020)
Co-BDC ([Co2(OH)2BDC], H2BDC = 1,4-benzenedicarboxylic acid) is known to possess metamagnetism originating from the antiparallel spins and high magneto crystalline anisotropy of Co(II).1 Herein, we have introduced a bimetallic concept by incorporating Ni(II) along with Co(II) in the same coordination polymer to modulate the magneto crystalline anisotropy in the lattice which in turn, affects the overall magnetic response of the coordination polymer. The Curie-Weiss equation fit suggested antiparallel arrangement of the spins (θ ≈ -62.5 K) of Ni(II) and Co(II) arranged in alternate fashion. The cusp in magnetization was observed at 7 K (Tc) with a significant coercive field of ∼750 Oe at 5 K.

Possible electron doping of geometrically perfect spin-1/2 kagome-lattice barlowite by reduced graphene oxide - Gupta, Kriti; Ninawe, Pranay; Jain, Anil; Dadwal, Arun; Anas, M.; Malik, V. K.; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Physical Review B, 2021)
Doping of quantum spin liquid (QSL) insulators by electron or hole leads to intriguing phase transitions to metallic and superconducting states. The barlowite family with geometrically perfect S = 1/2 kagome planes and tunable interkagome coupling is an emerging platform to realize spin-ordered, valence bond crystal, QSL states. Theoretical investigations on electron doping revealed localized states in the band gap of barlowite unlike metallicity in cuprate (Nd2CuO4). We present successful anchoring of phase-pure barlowite crystallites onto reduced graphene oxide (rGO). The resulting barlowite-rGO system was found to be an electrical semiconductor with Arrhenius activation energy of 0.07 eV. Semiconducting properties of the barlowite-rGO system were further modulated with retention of structural integrity. We have attributed such a transformation of electrical transport response to plausible electron doping thereby making charge-doping experiments on barlowite and its analogs propitious.

Seed-mediated growth of Pt on high-index faceted Au nanocrystals: the ag lining and implications for electrocatalysis - Roy, Debashree; Rajendra, Ranguwar; Gangadharan, Pranav K.; Pandikassala, Ajmal; Kurungot, Sreekumar; Ballav, Nirmalya (ACS Applied Nano Materials, 2021)
Bimetallic Au@Pt nanocrystals (NCs) offer a unique combination of plasmonic and catalytic properties and are a growing field of research. Herein, we report an unusual observation in the behavior of silver ions (Ag+) which was found to play a dominant role in dictating the Pt deposition in a seed-mediated growth method. `While the literature is replete with various instances of Ag-assisted Pt deposition whereby higher concentration of Ag+ translates into a thicker Pt shell, in the present study, contradictory observations were made. In the presence of lower amounts of Ag+, thick Pt shells were visualized, while at higher concentrations of Ag+, the extent of Pt deposition via the galvanic replacement reaction was reduced. Additionally, the presence of Ag was deemed necessary for the Pt deposition to take place, either in the form of an underpotential deposition layer on the Au NCs or by introducing Ag+ in the growth solution. We have demonstrated our findings on two different Au NCs enclosed with high-index facets, concave cuboid, and elongated tetrahexahedra, which mirror similar observations and provide generality to our claim. To the best of our knowledge, the time required for Pt deposition on the Au core in the present work is the least among the reported seed-mediated routes. Furthermore, this work, besides presenting a facile and general route for the amalgamation of catalytic and plasmonic properties in hybrid Pt-Au NCs, sheds light on the mechanistic aspects of Ag-assisted wet-chemical generation of bimetallic Au@Pt NCs. The overall electrocatalytic performance of our Au@Pt NCs toward the oxygen reduction reaction was realized to be impressive.
Keywords: bimetallic nanostructure; galvanic replacement reaction; high-index facet; oxygen reduction reaction; seed-mediated growth; underpotential deposition

Intertwining of localized (d) and delocalized (π) spins in magnetically frustrated two-dimensional metal-organic frameworks - Ugale, Ajay; Ninawe, Pranay; Jain, Anil; Sangole, Mayur; Mandal, Rimpa; Singh, Kirandeep; Ballav, Nirmalya (Inorganic Chemistry, 2024)
Two-dimensional metal-organic frameworks (2D MOFs) are emerging as a new class of multifunctional materials for diversified applications, although magnetic properties have not been widely explored. The metal ions and organic ligands in some of the 2D MOFs are arranged in the well-known Kagome lattice, leading to geometric spin frustration. Hence, such systems could be the potential candidates to exhibit an exotic quantum spin liquid (QSL) state, as was observed in Cu-3(HHTP)(2) (HHTP = hexahydroxytriphenylene), with no magnetic transition down to 38 mK. Hereto, we have investigated the spin intertwining in a bimetallic 2D MOF system, M-3(HHTP)(2) (M = Cu/Zn)(,) arising from the localized (d-electron) and delocalized (pi-electron) S = 1/2 spins from the Cu(II) ions and the HHTP radicals, respectively. The origin of the spin frustration (down to 5K) was critically examined by varying the metal composition in bimetallic systems, CuxZn3-x(HHTP)(2) (x = 1, 1.5, 2), containing both S = 1/2 and S = 0 spins. Additionally, to gain a deeper understanding, we studied the spin interaction in the pristine Zn-3(HHTP)(2) system containing only S = 0 Zn(II) ions. In view of the quantitative estimate of the localized and delocalized spins, the d-pi spin correlation appears essential in understanding the unusual magnetic and/or other physical properties of such hybrid organic-inorganic 2D crystalline solids

Robust spin liquidity in 2D metal-organic framework Cu3 (HHTP)2 with S=1/2 kagome lattice - Ninawe, Pranay; Jain, Anil; Sangole, Mayur; Anas, Mohd; Ugale, Ajay; Malik, Vivek K.; Yusuf, Seikh M.; Singh, Kirandeep; Ballav, Nirmalya (Chemistry- a european journal, 2024)
On one hand electron or hole doping of quantum spin liquid (QSL) may unlock high-temperature superconductivity and on the other hand it can disrupt the spin liquidity, giving rise to a magnetically ordered ground state. Recently, a 2D MOF, Cu-3(HHTP)(2) (HHTP - 2,3,6,7,10,11-hexahydroxytriphenylene), containing Cu(II) S = 1/2 frustrated spins in the Kagome lattice is emerging as a promising QSL candidate. Herein, we present an elegant in situ redox-chemistry strategy of anchoring Cu-3(HHTP)(2) crystallites onto diamagnetic reduced graphene oxide (rGO) sheets, resulting in the formation of electron-doped Cu-3(HHTP)(2)-rGO composite which exhibited a characteristic semiconducting behavior (5 K to 300 K) with high electrical conductivity of 70 S . m(-1) and a carrier density of similar to 1.1 x 10(18) cm(-3) at 300 K. Remarkably, no magnetic transition in the Cu-3(HHTP)(2)-rGO composite was observed down to 1.5 K endorsing the robust spin liquidity of the 2D MOF Cu-3(HHTP)(2). Specific heat capacity measurements led to the estimation of the residual entropy values of 28 % and 34 % of the theoretically expected value for the pristine Cu-3(HHTP)(2) and Cu-3(HHTP)(2)-rGO composite, establishing the presence of strong quantum fluctuations down to 1.5 K (two times smaller than the value of the exchange interaction J).
Keywords: 2D Metal-organic Framework; Electron doping; Reduced graphene oxide; Spin Liquid; Spin-frustration

Unconventional hole doping of S = ½ kagome antiferromagnet CoCu3(OH)6Cl2 - Mandal, Rimpa; Ninawe, Pranay; Ananthram, K. S.; Mhase, Akash; Gupta, Kriti; Saha, Sauvik; Ugale, Ajay; Singh, Kirandeep; Tarafder, Kartick; Ballav, Nirmalya (Advanced Physics Research, 2024)
Geometrically perfect S = ½ kagome lattices with frustrated magnetism are typically electrical insulators. Electron or hole doping is predicted to induce an exotic conducting state including superconductivity. Herein, an unconventional strategy of doping an S = ½ kagome lattice CoCu3(OH)6Cl2 is adopted – a structural analogue of a well-known quantum spin liquid (QSL) candidate herbertsmithite (ZnCu3(OH)6Cl2) – by integrating it with reduced graphene oxide (rGO) via in situ redox chemistry. Such an integration drastically enhances the electrical conductivity, resulting in the transformation of an insulator to a semiconductor, corroborating the respective density of states obtained from the density functional theory calculations. Estimation of the magnetic moments, data on the Hall-effect measurements, Bader charge analysis, and photoemission signals, altogether provide a bold signature of remote hole doping in CoCu3(OH)6Cl2 by rGO. The remote doping provides an alternative to the site doping approach to impart exotic electronic properties in spin liquid candidates, specifically, the generation of topological states like Dirac metal is envisioned.